PHYTOCHEMICAL SCREENING AND ΑLFA AMYLASE INHIBITORY ACTIVITY OF ORTHOSIPHON STAMINEUS AND ANNONA MURICATA LEAF ETHANOLIC FRACTIONS - Baiq Risma Fatmayanti; Sri Wardiatul Fitri; Arief Rafsanjani (Meditory : The Journal of Medical Laboratory, 2026)
Background: Orthosiphon stamineus and Annona muricata are medicinal plants traditionally used for diabetes management because they contain bioactive compounds capable of inhibiting carbohydrate-hydrolyzing enzymes. Objective: This study investigated the phytochemical composition and in vitro α-amylase inhibitory activity of the ethanolic leaf fractions of O. stamineus and A. muricata, individually and in combination. Methods: Leaf powders were extracted by methanol maceration, followed by liquid–liquid partitioning using n-hexane and 96% ethanol to obtain the ethanolic fractions. Phytochemical screening and an in vitro experimental study of fractions to α-amylase inhibition assays were performed individually and in combinations, with acarbose as the positive control. Data were analyzed using one-way ANOVA followed by Tukey's HSD test (p < 0.05). Results: Both ethanolic fractions contained alkaloids, flavonoids, and tannins. O. stamineus showed the highest α-amylase inhibitory activity (64.67%), followed by A. muricata (26.98%) and the 2:1 combination (59.74%), whereas the 1:1 combination exhibited the lowest inhibition (12.68%). Significant differences were observed among all treatments (p < 0.05). Conclusions: O. stamineus demonstrated greater α-amylase inhibitory activity than A. muricata. Combining the two extracts did not improve α-amylase inhibition compared with O. stamineus alone under the experimental conditions evaluated.